Effect of sintering temperature on phase formation, microstructure and dielectric properties of nanogold modified barium titanate ceramics - Jeeranan Nonkumwong (2018)
In this work, BaTiO 3 ceramics modified with 0.5 mol% Au nanoparticles were fabricated by using a combination of the solid-state reaction and pressureless-sintering techniques. By employing a combination of X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray (EDX), Archimedes principle and dielectric measurement techniques, it was found that no phases other than tetragonal BaTiO 3 were observed in all ceramics. In contrast to the tetragonality, the relative density, grain size and maximum dielectric constant at Curie temperature of the ceramics were found to increase with sintering temperature. In addition, it has been found that, under suitable sintering temperature, dense perovskite nanogold modified BaTiO 3 ceramics with fine-grained microstructure (∼1 μm) and better dielectric properties than those of gold-free ceramics can be produced.© 2014 Elsevier B.V. All rights reserved.